Perencanaan dan Pelaksanaan Supervisi Akademik Pendidikan Agama Islam - Suhaimi, Suhaimi (SYAMIL: Journal of Islamic Education, 2017)
In an effort to produce a quality lesson that is run by teachers, the steps taken in the education system is an intense and continuous coaching in the form of academic supervision given to teachers to improve their ability to run a quality learning process. Guidance to the teacher's essence is an act of giving assistance to improve his ability in running the learning process. The reason for coaching is given to the teacher is that the ability of the teacher must always be improved especially in the techniques related to the learning process that must be executed. The failure of teachers in the learning process is more due to the ability of teachers who are still low in the science of teaching. It may be that the teacher has had enough qualifications or even master's degrees, but is still weak in his teaching. So the ability of teachers in running a quality learning process is still low. Suharsimi Arikunto asserted that the main activity of supervision is to provide guidance to the school/madrasah in general and especially to the teachers for better learning quality, which in turn improves students' learning achievement. in the Government Regulation Number 19 Year 2005 on Education Standards specially contained in Chapter IV Article 19 paragraph (3) states that every year education performs planning of learning process, implementation of learning process, assessment of learning activity, and supervision of learning process for the implementation of effective learning process and efficient.